Development of an Environment-Based Electronic Worksheet for Chemical Equilibrium Practicum - Selviana Putri; Fitriani Fitriani; Dini Hadiarti (Jurnal Pendidikan Terapan, 2026)
Purpose: This research aims to develop an environmentally based practicum E-LKPD (electronic student worksheet) on Chemical Equilibrium material to address laboratory facility limitations and produce a valid, practical product with potential to improve students' conceptual understanding. Methods: This study used the Research and Development (R&D) method with a 3D model (Define, Design, Develop) modified from the 4D model. Subjects were 11th-grade high school students, involving a small-scale trial (9 students) and a large-scale trial (27 students) selected via purposive sampling. Data were collected through expert validation sheets, student response questionnaires, and pretest-posttest questions, then analyzed using validity and practicality percentages and Normalized Gain (N-gain). Findings: The E-LKPD was rated very valid by media experts (95.83%) and material experts (94.44%), and very practical based on student responses (86.36% small-scale; 87.04% large-scale). Average N-gain of 0.90 (small-scale) and 0.92 (large-scale), both in the high category, indicated the E-LKPD's potential to improve conceptual understanding. Research Limitations: This research was conducted in only one class at one school without a comparison group, so generalizability remains limited and further research in a broader context is needed. Research Implications: This E-LKPD can serve as an economical, applicable, and environmentally friendly alternative teaching material for chemistry teachers, particularly in schools with limited laboratory facilities, enabling more contextual and interactive chemical equilibrium learning. Originality: This research develops an environment-based practicum E-LKPD integrating local environmental potential with interactive digital features for chemical equilibrium learning, an approach still relatively rare in previous studies.